Kelayakan Isi Teks Deskripsi Bermuatan Lokal dalam Buku Jelajah Desa Wisata Anugerah Indonesia sebagai Bahan Bacaan Siswa SMP - Nur Saidah; Asep Purwo Yudi Utomo (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study is to examine the feasibility of the content of local content descriptive texts in the book Jelajah Desa Wisata Anugerah Indonesia as reading material for junior high school students. The content feasibility criteria refer to BSKAP (2022) regarding the content feasibility criteria for local content textbooks. There are four criteria used in this study, including (1) scientific truth; (2) conformity with established local content documents; (3) conformity with developments in science and technology; and (4) conformity with the context and environment. Theoretically, this study uses a content feasibility approach and methodologically uses a qualitative descriptive approach. The data used in this study are 19 local content descriptive texts sourced from the book Jelajah Desa Wisata Anugerah Indonesia from the Ministry of Tourism and Creative Economy (Kemenparekraf). From these data, the researcher conducted data analysis using the matching method. The data collection technique used was reading and note-taking. Data presentation was carried out using formal and informal presentation methods. Then, in the second, third, and fourth criteria, 19 texts were in accordance, and there were no incompatible texts. The benefits of this study are to enrich the study of the eligibility of the content of local-containing descriptive texts in reading learning in junior high schools, as a reference for determining and developing reading materials for local-containing descriptive texts, and to contribute to efforts to preserve local wisdom through the use of the book Jelajah Desa Wisata Anugerah Indonesia as a source of literacy.